STUDI ANALISIS ISI PROGRAM #PLASTICSMARTCITIES SEBAGAI EDUKASI LINGKUNGAN PADA INSTAGRAM @WWF_ID - Nisrina Nuha Nazira (2023)
The World Wide Fund for Nature (WWF) Indonesia has initiated a program called Plastic Smart Cities with the aim of informing and educating the public about reducing plastic leakage into the environment by 30% in the near future and eliminating plastic by 2030. One of the platforms used to deliver this education is the social media platform Instagram, specifically the account @wwf_id. This research aims to describe the environmental education content on Instagram @wwf_id with the hashtag #PlasticSmartCities during the period of July-November 2022, based on indicators from three dimensions of environmental education: knowledge and experience, skills, and attitudes and behaviors. The research utilizes a quantitative approach and content analysis method. The units of analysis in this study consist of 12 image posts with a total of 64 images, and 7 video posts divided into 64 scenes. For image content, there are 55 communications (messages), and 37 uploader factors (emotions). For video content, there are 64 image scenes, 62 audio elements, and 16 animations. The data is analyzed descriptively and presented in the form of frequency and percentage tabulations. Two coders were involved in the coding process to maintain objectivity, and intercoder reliability was measured using Scott's formula. The results show that the #PlasticSmartCities content contains a significant amount of environmental education in image posts, with the communication (message) category accounting for 98,18% and the uploader factor (emotion) category accounting for 88,89%. In video posts, environmental education is found in the text element at 88,64%, image at 95,31%, audio at 54,83%, and animation at 68,75%. The reliability test results indicate that the highest reliability value is found in the video unit of analysis for the text, audio, and animation elements, while the lowest value is found in the image content in the uploader factor (emotion) category. In conclusion, the #PlasticSmartCities content on WWF Indonesia's Instagram account effectively portrays environmental education with the highest dimension values being knowledge and experience.